2011
DOI: 10.1016/j.beproc.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Repeated extinction and reversal learning of an approach response supports an arousal-mediated learning model

Abstract: We assessed the effects of repeated extinction and reversals of two conditional stimuli (CS+/CS−) on an appetitive conditioned approach response in rats. Three results were observed that could not be accounted for by a simple linear operator model such as the one proposed by Rescorla and Wagner (1972): (1) responding to a CS− declined faster when a CS+ was simultaneously extinguished; (2) reacquisition of pre-extinction performance recovered rapidly within one session; and (3) reversal of CS+/CS− contingencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Interestingly, when the previous trial was reinforced, control and chronically stressed rats showed similar response latencies. This interaction effect between reinforcement and stress on response latency suggests a ceiling effect of reinforcement on behavioral activation (Salomon & Correa, 2002), and a differential effect of stress on rate of decline in activation in the absence of reinforcement (Killeen, Hanson, & Osborne, 1978; Podlesnik & Sanabria, 2011). That is, chronic stress appeared to speed up the spontaneous decline in behavioral activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when the previous trial was reinforced, control and chronically stressed rats showed similar response latencies. This interaction effect between reinforcement and stress on response latency suggests a ceiling effect of reinforcement on behavioral activation (Salomon & Correa, 2002), and a differential effect of stress on rate of decline in activation in the absence of reinforcement (Killeen, Hanson, & Osborne, 1978; Podlesnik & Sanabria, 2011). That is, chronic stress appeared to speed up the spontaneous decline in behavioral activation.…”
Section: Discussionmentioning
confidence: 99%
“…That is, chronic stress appeared to speed up the spontaneous decline in behavioral activation. This effect may have important implications for stress-related learning deficits (Podlesnik & Sanabria, 2011; Touyarot, Venero & Sandi, 2004) and tolerance to the reinforcing properties of drugs of abuse (Koob & Le Moal, 2001). This effect is also consistent with the notion that chronic stress reduces incentive motivation, as reported on a progressive ratio schedule (Kleen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As this study and others [17-19] indicate, free operant responding is composed of multiple underlying components that change over the course of extinction. These changes may reflect the numerous processes implicated in extinction learning, such as reductions in arousal or incentive motivation [28-30], and learning new associations in an unreinforced context [31,32], among many others (see [31,33] for reviews). A precise mapping of these processes to changes in response-bout microstructure during extinction [18] would provide a foundation for inferences about the processes responsible for differences in performance between strains.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the reinforcer has been interpreted to imply the absence of reinforcer-elicited arousal (Killeen et al 1978; Killeen 1998); the absence of the response-outcome contingency has been interpreted to imply the acquisition of a new response-no outcome association (Bouton 2004; Rescorla 2001). How each of these psychological processes, de-motivation and extinction learning, contribute to the decline in response rate is fundamental to the construction of learning models (Podlesnik and Sanabria 2010). …”
Section: Introductionmentioning
confidence: 99%